Smart materials and structures - a finite-element approach: a bibliography (1986-1997) - Mackerle, Jaroslav (Modelling and simulation in materials science and engineering, 1998)
This paper gives a bibliographical review of the finite-element methods (FEMs) applied to the analysis and simulation of smart materials and structures. The bibliography at the end of the paper contains references to papers, conference proceedings and theses /dissertations on the subject that were published between 1986-1997. The following topics are included: smart materials; smart components/structures; smart sensors and actuators; controlled structures technology; and other topics.